ANALISIS PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA ( SEKTOR PERDAGANGAN, HOTEL DAN RESTORAN ) DI KOTA BATU - Cori Akouino (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
Target of this research is to analyse impact change of commercial sector added value, restaurant and hotel in absorbtion of labour in Batu City year 2002-2011. This research use method research of analysis of regressi doubled linear. Result of research indicate that there is positive influence between PDRB commercial sector, restaurant and hotel (X) to Labour in commercial sector, restaurant and hotel (Y) equal to 43%. Becoming if PDRB commercial sector, restaurant and hotel (X) mount equal to 1 % of hence Labour in commercial sector, restaurant and hotel (Y) will go up equal to 43% conversely if commercial sector, restaurant and hotel (X) equal to 1 % of hence Labour in commercial sector, restaurant and hotel ( Y) will go down equal to 43% with other variable assumption remain to.